Unveiling surface stability and oxygen diffusion of rare‐earth zirconate pyrochlores by density functional theory. Issue 4 (22nd December 2022) - Zhao, Juanli; Ching, Wai‐Yim; Lai, Mengling; Fan, Yun; Li, Jiancheng; Li, Yiran; Li, Wenxian; Liu, Bin
Abstract: The surface structures, bond variations, and segregation of oxygen vacancies play crucial roles in the structural stability and functionality of nanocrystalline rare‐earth zirconate pyrochlores. In this work, the stabilities of (1 0 0), (1 1 0), and (1 1 1) surfaces of pyrochlore A 2 Zr2 O7 ( A = La, Ce, Pr, Nd, Pm, Sm, Eu, or Gd) are investigated by first‐principles calculations. Surface reconstruction occurs on (1 1 0) surface with a transition of ZrO6 octahedron to ZrO4 tetrahedron, leading to their large relaxation energies. In combination with the small amount of broken bonds during the surface formation process, the (1 1 0) surfaces are identified having the lowest surface formation energies than the (1 0 0) and (1 1 1) surfaces. Moreover, the reconstructed (1 1 0) surface has characteristics of the segregation of oxygen vacancies. The surface oxygen vacancies have the low migration barriers (<1.2 eV), which are comparable with those in bulk and ensure the long‐distance diffusion of oxygen vacancies in A 2 Zr2 O7 . These discoveries provide fundamental insight to the surface structure and related oxygen vacancy behavior, which are expected to guide the optimization of the surface related properties for nanocrystalline rare‐earth zirconates.